KONSEP PAYANGO PADA RUMAH TINGGAL TRADISIONAL DI GORONTALO - Umar; Emil Fatra; Thiara Tri Funny Manguma (Yayasan Sagita Akademia Maju, 2024)
Gorontalo, a province located in the north of the island of Sulawesi, has a form of cultural custom regarding the procedures for making a building which has a very important meaning in development, called the concept of